La historia descifrada: Derivaciones Latinoamericanas de los archivos de Moscú - Kersffeld, Daniel (2016)
With the end of the Soviet Union, the Archives of the International Communist were opened to public consultation, until that time they were only reserved for the reading and review by a few leaders and communists specialists. This is a big amount of documents with unconcealable political, economic, social and cultural references with a significant impact both in history and historiography of the 20th century. But the influence generated by these files in Latin America was also very high were the documents began to be explored in detail just in the past few years. Taking as its axis the life of the communist parties, the files are stray in a deep reading about the various national realities in which the different emissaries of Moscow had to act, taking into account in detail all kind of particularism that either could contribute to the development of the revolutionary and socialist project or instead could hinder even forcing them back. This article outlines the historical implications surrounding the opening of these files as well as those items and elements to be reviewed on a possible agenda highlights for analyzing present and future of our societies.